Novel multi-rate multicast congestion control algorithm - ZHANG Deng-yin; WANG Qian-qian; LI Jun; WANG Ru-chuan (Tongxin xuebao)
A novel congestion control mechanism based on packet-bunch probe and TCP throughput formula（PTMCC） was proposed.This receiver-driven multi-rate multicast congestion control mechanism probes available bandwidth by packet-bunch and gets TCP-friendly rate by TCP throughput formula.A new rate adjustment algorithm was also designed.Simulation results show that the PTMCC make good performance on convergence,TCP-friendliness and response to congestion.